ANALISIS PENERAPAN SISTEM PENGELOLAAN DANA TERPADU MUHAMMADIYAH - Ahmad Said; Eko Susanto; Andi Amri (Universitas Muhammadiyah Prof Dr Hamka, 2022)
This research is motivated by an analysis of the organizational structure of fund management in Muhammadiyah which is autonomous, individual and egalitarian so that the management of funds is left to each institution/business charity under Muhammadiyah. The purpose of this study is to obtain information on how effective the Muhammadiyah cash management integrated fund management system is in collecting business charity funds, to find out the factors that influence the implementation of an integrated fund management system for cash management services, and to identify and analyze how much benefit is felt from the integrated fund management system. Muhammad. The method used is an analytical-identification method. Data collection techniques through two stages and the types of data used are primary data and secondary data. The results show that institutional liquidity for public perception has a significant influence on the level of benefit, profits for respondents' perceptions and suggestions have a significant influence on the level of benefit, member satisfaction for community perceptions has an insignificant effect on the level of benefit, member involvement for community perceptions has a significant influence on the level of benefit, and business sustainability has a significant influence on the level of benefit. Keywords; Implementation, Management, Integrated Fund, Business Charity, Muhammadiyah.